Marketing Strategy By Rice Craps As A Culinary Tourism In Digital Era In Economic Development Creative Based Local Wisdom - Uswah Hasanah; Efry Kurnia (Proceeding International Seminar of Islamic Studies, 2019)
Currently the backbone of the economy of developed countries is in creative societies. This is because the creative community will spark various ideas in the economic development of the community. The important role of this generation is to encourage change in each era, moving towards constructive and becoming a moral force that will oversee every nation's journey in its development. Muslim Millennia generation of creative ideas and innovation are expected to be able to provide solutions to the nation's problems, namely poverty and unemployment. Until now, poverty unemployment, massive exploitation of nature which ultimately led to inequality both in terms of social and economic growth is still a classic problem that requires a solution. Rice crust has contributed to moving the home industry business sector and marketing services. And is a revitalization of the value of local wisdom of the Indonesian people in the context of the creative economy.